(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: A key goal of exercise and physical therapy (EPT) is to enable individuals to be physically active. However, many rehabilitation patients struggle to maintain adequate physical activity levels after completing rehabilitation. Promoting individual competencies for initiating and maintaining a physically active lifestyle is a promising strategy for long-term physical activity promotion. Yet, it is unclear to what extent competencies such as Physical Activity-Related Health Competence (PAHCO) are considered in EPT. This contribution aims to describe the status quo of EPT with a focus on physical activity promotion in three rehabilitation centres in Bavaria, Germany. Methods: To collect information about rehabilitation patients’ experiences with EPT focused on physical activity promotion, a Patient-Reported Experience Measure (PREM) questionnaire was developed. The questionnaire includes 11 items, answered on a five-point Likert scale, covering the components of PAHCO and the action model for PAHCO promotion. Analogously, a Therapist-Reported Action Measure (TRAM) questionnaire was developed to assess therapists’ actions in the three domains of implementation, attitude, and competence in relation to focusing PAHCO in EPT. Each TRAM domain comprises 11 items, analogous to the PREM items. The data were analysed descriptively. Results: Overall, both rehabilitation patients (n = 222; Mrange = 3.54 to 4.62) and therapists (n = 36; Mrange = 3.00 to 4.60) reported moderate-to-high levels of PAHCO-focused EPT implementation. Notably, elements related to planning and maintaining physical activity appeared to be implemented less than those involving the execution of physical activity, as reported by patients and therapists. While the implementation of a PAHCO-focused EPT (Mdiff = 0.61) showed differences between the rehabilitation centres, as reported by therapists, their ratings in terms of attitude (Mdiff = 0.30) and competence (Mdiff = 0.32) were rather similar across all centres. Conclusion: These findings highlight both strengths and areas for improvement in EPT regarding physical activity promotion in three Bavarian rehabilitation centres. The limited emphasis on planning and maintaining physical activity may represent a missed opportunity to support sustained behavioural change in patients. Additionally, variability in implementation across centres suggests the need for more standardised and comprehensive EPT concepts to enhance physical activity promotion in medical rehabilitation settings. Support/Funding Source: German Pension Insurance Bavaria North, German Pension Insurance Bavaria South.